Carbohydrate-naphthalene diimide conjugates as potential antiparasitic drugs: Synthesis, evaluation and structure-activity studies - Zuffo, M; Stucchi, A; Campos-Salinas, J; Cabello-Donayre, M; Martínez-García, M; Belmonte-Reche, E; Pérez-Victoria, J M; Mergny, J L; Freccero, M; Morales, J C; Doria, F (European journal of medicinal chemistry, 2019)
The neglected tropical diseases Human African Trypanosomiasis and leishmaniasis are caused by infection with trypanosomatid parasites Trypanosoma brucei and Leishmania spp, respectively. The genomes of these organisms contain multiple putative G-quadruplex (G4) forming sequences which have recently been proposed to mediate processes relevant for parasite survival. Therefore, G4 could be considered as potential targets for a novel approach towards the development of antiparasitic drugs. Recently, we have demonstrated that G4 ligands such as carbohydrate naphthalene diimide conjugates (carb-NDIs) possess notable antiparasitic activity. Herein, we have synthesized a new family of carb-NDIs, characterized by significant structural variability, and evaluated their anti-parasitic activity, with special focus on T. brucei. The interaction with relevant G4 sequences was evaluated in vitro through independent biophysical methods (FRET melting assays under competing conditions with double stranded DNA, circular dichroism and fluorescence titrations). Finally, flow cytometry and confocal microscopy experiments demonstrated that the conjugates exhibit excellent uptake into T. brucei parasites, localizing in the nuclei and kinetoplasts. Promising antiparasitic activity and selectivity against control mammalian cells, together with their peculiar mechanism of action, render the carb-NDI conjugates as suitable candidates for the development of an innovative treatment of trypanosomiasis.
Keywords: Animals; trypanozomiáza; sacharidy; buněčné linie; Leishmaniasis; Imides; Structure-Activity Relationship; lidé; leishmanióza; Antiparasitic Agents; Carbohydrates; imidy; Cell Line; G-kvadruplexy; Naphthalene diimide; Naphthalenes; Trypanosoma brucei brucei; G-Quadruplexes; Trypanosoma brucei; antiparazitární látky; naftaleny; vztahy mezi strukturou a aktivitou; Trypanosomiasis; zvířata; G-quadruplex (G4); Antiparasitic activity; Humans